2005
DOI: 10.1007/s00122-005-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity of European flint maize populations determined with SSR analyses of individuals and bulks

Abstract: Landraces of maize represent a valuable genetic resource for breeding and genetic studies. Using simple sequence repeat (SSR) markers, we analysed five flint maize populations from Central Europe that had played an important role in the pre-hybrid era in Germany. Our objectives were to (1) investigate the molecular genetic diversity within and among the populations based on the SSR analysis of individuals, (2) compare these results of the SSR analysis based on individuals with those based on bulks, (3) examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 27 publications
11
62
3
Order By: Relevance
“…Altogether we found 13.13 alleles per locus, which is higher than the value reported by Aci et al (2013) among Algerian populations or Romay et al (2012) among Spanish germplasm with the same SSR set of loci. The number of alleles per locus was also higher than that reported in other American origins with different SSRs (Reif et al, 2003b(Reif et al, , 2004(Reif et al, , 2005(Reif et al, , 2006Wiethotler et al, 2008;Bracco et al, 2012).…”
Section: Resultsmentioning
confidence: 48%
“…Altogether we found 13.13 alleles per locus, which is higher than the value reported by Aci et al (2013) among Algerian populations or Romay et al (2012) among Spanish germplasm with the same SSR set of loci. The number of alleles per locus was also higher than that reported in other American origins with different SSRs (Reif et al, 2003b(Reif et al, , 2004(Reif et al, , 2005(Reif et al, , 2006Wiethotler et al, 2008;Bracco et al, 2012).…”
Section: Resultsmentioning
confidence: 48%
“…This could be explained by the fact that alleles present in small percent can be missed in bulk analysis (Reif et al, 2005). In IP1 and IP2 accessions an unknown band (allele) was detected, positioned between the o2 and O2 bands.…”
Section: Discussionmentioning
confidence: 99%
“…Better agreement with expected results was accomplished with AFLP analysis (Figure 3). In the work of Reif et al (2005) it was suggested that SSR analysis of bulked populations cannot detect alleles with a frequency below 0.2, so that a large number of alleles with low frequencies remains undetected. They also concluded that differences between populations are emphasized due to a concentration on alleles with high frequencies.…”
Section: Molecular Marker Analysismentioning
confidence: 99%
“…The results in our work which indicate that SSRs are not a good choice for bulk analysis of populations could be explained by several reasons, besides the low sensitivity of bulk approach in detecting low frequency alleles. Use of di-nucleotide repeat SSR (excluded in the work of Reif et al, 2005) which tend to be more polymorphic than SSR with longer repeat motifs (Smith et al, 1997) could have caused higher scoring errors. The silver staining of the gels is probably not the right choice for bulk analysis due to its low sensitivity.…”
Section: Molecular Marker Analysismentioning
confidence: 99%
See 1 more Smart Citation